(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This thesis examines the advantages and disadvantages of using multimedia technologies in the educational process. Multimedia technologies have become an important component of modern education because they combine text, sound, images, animation, video, interactive tasks, and digital communication tools. Their use increases students’ motivation, improves visualization of complex concepts, supports different learning styles, and creates opportunities for interactive and independent learning. At the same time, the excessive or methodologically incorrect use of multimedia may cause distraction, superficial understanding, technical dependence, reduced live communication, and unequal access to digital resources. The thesis analyzes multimedia technologies from pedagogical, methodological, psychological, and organizational perspectives. The results show that multimedia tools are effective when they are integrated into the educational process purposefully, according to learning objectives, students’ age characteristics, subject content, and didactic principles.